OPTIMALISASI USAHATANI SAYUR TUMPANGSARI DI DESA SUKORAMBI KECAMATAN SUKORAMBI KABUPATEN JEMBER - Berilisda Jepatrika Dirga Buana; Anik Suwandari (University of Jember, 2020)
The implementation of intercropping systems is considered by farmers to be able to overcome the problem of low productivity and fluctuations in vegetable prices. The purpose of this study was to determine Combination of intercropping vegetable farming that provides maximum benefits. The determination of the study area was carried out using a purposive method. The sampling technique uses quota sampling. The method of analysis uses linear programming. The results showed that (1) the maximum benefit of the intercropping model 1 was obtained by planting green mustard and spinach, the intercropping model 2 planting green mustard, spinach and kale, the intercropping model 3 planting green mustard, spinach and basil, the intercropping model 4 planting spinach, green mustard, marigolds and basil. (2) Rare production factors are spinach land on intercropping models 1, 2, 3 and 4, basil land on intercropping model 4, ZA fertilizer on intercropping model 1, manure on intercropping models 2, 3 and 4, callicron pesticide on intercropping model 2 and 4 as well as the amnistar top pesticides in intercropping model 3. (3) The highest increase in maximum profit conditions is in the intercropping model 4 by 15.7% and the lowest in the intercropping model 1 by 13.6%.